Narrative interventions in the framework of Manifesta 14 reviving and questioning the murky collective memory in Prishtina. - Seebass, Frauke M.; Mehmeti, Arban (Journal of Southeast European & Black Sea Studies, 2025)
In the strive for self-determination and European integration, Kosovo's elites have been keen to suppress the Ottoman and Yugoslav heritages and memories in support of a Euro-Atlantic future. As Prishtina's residents fight an ongoing 'battle for public space,' long-forgotten places that have fallen into oblivion become sites where alternative narratives can emerge, engaging various generations in contesting dominant historical narratives. This is the declared objective of the Urban Arts Biennale MANIFESTA which was hosted in Prishtina in the summer of 2022, bringing together international artists, academics and activists with the aim of reviving and claiming forgotten public spaces and investigating the narratives surrounding them.